(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the effect of servant leadership on Service Oriented - Organizational Citizenship Behavior (SO-OCB) with trust in leaders as a mediating variable in 3 and 4 star hotel employees in Padang City. This study uses a quantitative approach with a survey method and distributes questionnaires to 180 hotel employees as respondents. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Square (SmartPLS 4). The independent variable in this study is servant leadership, the mediating variable is trust in leaders, and the de- pendent variable is SO-OCB. The results of this study indicate that: Servant Leadership has a positive and significant effect on Trust in leaders, Trust in leaders has a positive but insignificant effect on SO-OCB, Servant Leadership has a positive and significant effect on SO-OCB, and Trust in leaders does not mediate the effect of Servant Leadership on SO-OCB.